(untitled) (Heteroglossia – studia kulturoznawczo-filologiczne, 2025)
The article presents the barbarization of the Polish language in public discourse, which can take the form of anglicization, understood as the overuse of English words and phrases, maintaining the voicing of consonants that become voiceless in certain positions, mimicking the semantic-syntactic structures of the English language, and the use of glottodidactic doublets (an author’s concept). The study focuses on spoken language only, with selected popular socio-political programs available on YouTube serving as the research material. In conclusion, it was found that the linguistic patterns provided in these programs contribute to the ongoing barbarization of the Polish language, of which anglicization is the main, but not the only, manifestation.